KRYTYKA PRÓB EMANCYPACJI ŚLĄSZCZYZNY. PŁASZCZYZNA NAUKOWA (LINGWISTYCZNA) - JAROSZEWICZ, HENRYK (Slavia Occidentalis, 2020)
Despite the numerous attempts made in the 21st century at gaining linguistic independence, the Silesian ethnolect still enjoys the official status of a dialect. Lack of success in the attempted emancipation should be attributed to the linguistic policy adopted by the Polish authorities and political elites. The attempts at emancipation of the language spoken in Silesia have been subjected to criticism on many levels of the social discourse including the academic level. However, a detailed analysis of the presented arguments is evidence that there are no objective, linguistic premises that questioning promotion of the Silesian ethnolect to the status of a regional language is unsubstantiated.